Coal fly ash-based geopolymer spheres coated with amoxicillin and nanosilver for potential antibacterial applications - Lira, Brandon Cyril S. (Animo Repository, 2019)
Geopolymers are emerging “green” materials for its low embodied energy and carbon footprint, and its potential to valorize wastes, such as coal fly ash. It is an inorganic cementitious material formed from the polymerization of aluminosilicates in an activating solution such as that of alkali hydroxides or silicates. Their superior mechanical properties, including heat and fire resistance make them an excellent material for diverse applications. Recent studies have also exploited the tunable open porosity and adsorbing properties of geopolymers. Our work thus explores the potential of porous geopolymer spheres for antibacterial applications. These spheres were synthesized using coal fly ash as the geopolymer precursor and the porous surface is coated with either amoxicillin or silver nanoparticles (AgNPs) adsorbed in the matrix. For the AgNP geopolymer spheres, SEM images show spherical nanostructures when using ascorbic acid as a reducing agent, while spherical, cubical, and wire structures were observed when reduced using NaBH4. Indication from UV-Vis results also suggests the gradual release of both amoxicillin and AgNPs in the solution from the functionalized geopolymer spheres. Using E. Coli as the test organism for a modified disk diffusion assay, both showed zones of inhibition against the bacteria. Further tests on antibacterial application of AgNP geopolymer spheres show their effectiveness to kill at least 95% of the E. coli in a water sample initially containing 105 cfu/mL in just 30 minutes. © 2019, Gadjah Mada University. All rights reserved.